The Interplay of Individual Factors, Mood, and Promotions in Shaping E-Impulsive Buying Behavior - Nanik Wahyuningtiyas; Tri Sugiarti Ramadhan (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to investigate the effect of individual factors, mood, and promotion on e-impulse buying behavior; or simply spontaneous and unreflective online purchases. Quantitative - A survey of 196 online consumers was deployed. Smart PLS software will be used to analyze the obtained data of partial least squares (PLS) based Structural Equation Model (SEM). The emotion factor also has a significant impact on individual factors, and promotion realized e-impulsive buying. Positive moods are inclined to proactivity and optimism - also in shopping, whereby attractive, appropriate promotions could even be responsible of a spurious purchase. The remaining four hypotheses did not demonstrate any relationship significantly. The personal factors of an individual have no direct effect on decisions to engage in online impulse purchasing and mood while affecting the personal factors, does not significantly affect e-impulsive buying. Also, the individual aspects do not reveal a clear signal as to whether marketing promotions have enough muscle on their own in changing consumer characteristics. Besides, the five indirect relationship hypotheses were not well supported so that each mediating variable had no significant influence on impulse shopping behavior online. In other words, because most online shoppers think before they buy and will need a clear reason to act in the moment. More investigation should be done, looking at other variables that in conjunction with the predictors of this research can improve our understanding about what influences click bait behavior so as to create more effective marketing strategies when it comes sharing content on e-commerce platforms.